2003
DOI: 10.1023/a:1022259011052
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Sustained delivery over 4 days and multiple sites allow a convenient, well-tolerated, twice-weekly OXY TDS dosing. A low incidence of anticholinergic side effects is expected during clinical use because of the avoidance of presystemic metabolism and low DEO plasma concentrations. The consistent delivery, absorption, and pharmacokinetics should result in an effective treatment of patients with overactive bladder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…This was also observed in human plasma after the system removal. 24) There have been no data available for this phenomenon, however, stimulation as a result of the removal could be one of the causes of this increase. However, it is not considered that the increase in receptor occupancy influences the effect in the bladder because the increase is relatively small.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was also observed in human plasma after the system removal. 24) There have been no data available for this phenomenon, however, stimulation as a result of the removal could be one of the causes of this increase. However, it is not considered that the increase in receptor occupancy influences the effect in the bladder because the increase is relatively small.…”
Section: Discussionmentioning
confidence: 99%
“…All the compounds were dissolved in saline. (R/S)-OXY transdermal delivery systems (12,24 and 48 mg/body as a free base) were applied for 48 h on the shaved backs of the rats after anesthetization with diethyl ether. Blood samples with heparin were collected via the tail vein after administration and centrifuged immediately.…”
Section: Pharmacokinetics/pharmacodynamics Analysis Of the Relationshmentioning
confidence: 99%
“…Under this incubation condition K m of 9.3 and 7.9 nmol L −1 for (R)-OXY and (S)-OXY, respectively, were observed indicating greater enzyme affinity to (S)-OXY and consequently, the enantioselective OXY biotransformation by rat liver microsomes. Previous studies have clearly demonstrated the enantioselective pharmacokinetic characteristics of OXY and DEO after oral or transdermal administration in man [5,6], however only one recent report described the in vitro stereoselective biotransformation of OXY using human microsomal fraction [9] as well as recombinant human P450-expressing microsomes. Comparing our preliminary results with those reported by Mizushima et al [9], the R/S ratio K m of OXY is similar in human and rat microsomes.…”
Section: Methods Applicationmentioning
confidence: 99%
“…DEO is present in the plasma at concentrations approximately 4-10 times higher than those of the parent compound and it has similar anticholinergic effects of OXY. In therapeutic use, DEO seems to contribute greatly to the anticholinergic side effects, in particular dry mouth [5,6]. The possibility of OXY delivering via non-oral route may be a more effective method of reducing the drug adverse reactions.…”
Section: Oxybutyninmentioning
confidence: 99%
See 1 more Smart Citation